PERLINDUNGAN HUKUM TERHADAP PEMAKAI OBAT KADALUARSA (Lex Journal: Kajian Hukum & Keadilan, 2018)
Health has a very important meaning for humans, and humans must maintain good health. Health can be maintained by taking drugs, drugs have a purpose and various. Circulation of drugs in the community a lot and the Drug and Food Supervisory Agency is authorized to supervise drug distribution in the community. The distribution of the drug must obtain a marketing permit from the Food and Drug Supervisory Agency and must include an expired date label.The more drugs in circulation, the public does not know the drugs have expired. If drug expiration circulates the authority of the Drug and Food Supervisory Agency to monitor and sanction. Users of expired drugs can be given recovery or compensation.